Psychological Well-Being, Prenatal Attachment, and Quality of Early Mother-Infant Interaction: A Pilot Study With a Sample of Mothers With or Without Cancer History - Laura Bozicevic; Lucia Ponti; Martina Smorti; Gabriella Pravettoni; Fedro Alessandro Peccatori; Chiara Cassani; Giuseppe Nastasi; Valentina Sarchi; Lucia Bonassi (Frontiers in Psychology, 2022)
Given the positive impact of high-quality mother–infant interaction on child development, and that such relationship might be hindered by maternal stresses such past cancer, research is needed to understand protective and risk factors in this clinical population. As almost no data is available on the impact of history of cancer on the quality of mother–infant interaction, a multicentric and longitudinal pilot study was conducted. Differences in women’s prenatal psychological well-being and attachment (T1, third trimester), and postnatal quality of mother–infant interaction (T2, 2–5 months) were assessed in a sample of Italian mothers with (N = 11) or without cancer history (N = 13). Results showed that women did not differ significantly in their prenatal well-being (assessed with the Profile of Mood States questionnaire) and levels of attachment (assessed with the Prenatal Attachment Inventory). Looking at mother–infant interactions (assessed using the Global Rating Scale at T2), while maternal sensitivity, warmth and intrusiveness, and infant distress and attentiveness did not differ between the two groups, in the clinical group, mothers were more remote and less absorbed in the infant, and infants showed fewer positive communications. These findings might shed light on potential protective and risk factors for early parenting and later child outcomes in this clinical population.